Analisis Metodologi Penulisan Litelatur Hadis Abad 3 H - Abdulatip, Tetep; Rafiq, Muhamad Chaedar; Fadllurrahman, Irfan; Nurlaela, Neni (Lembaga Yasin AlSys, 2024)
This paper aims to reveal the methodology of Hadith literature writing in the 3rd century Hijri. The research method used is qualitative, gathering written data sources both primary from books and secondary from online digital sources, with a library research approach to facilitate the compilation of this article. The results of this study uncover that the methodology of Hadith literature writing that developed in the 3rd century Hijri includes the compilation of Al-Musnad books, As-Sahih books, and Al-Jami' books.